Explore Chinese lacquer art culture–eggshell inlay technique / Rao DongYu, Prof. Madya Dr. Azahar Harun and Li YiXuan - Rao, DongYu; Harun, Azahar; Li, YiXuan (Universiti Teknologi MARA, Kedah, 2025)
Chinese lacquer art is one of the treasures of Chinese traditional art. In China's 5000 years of profound history, eggshell inlay is an exquisite and complex conventional skill. This paper analyses the eggshell inlay technique, introduces technical elements from material selection and special tools to practical application, and describes its creative process, highlighting this traditional process's wisdom and unique artistic expression. This paper emphasises the application and artistic attraction in diversified application scenarios through comprehensive analysis and research on the conventional function and deep-rooted cultural value of eggshell inlay. It aims to deepen the detailed analysis of Chinese lacquer eggshell inlay technique, to clearly understand its cultural connotation and the quality of its artworks, and intuitively express its prominent position and far-reaching significance in Chinese and global cultural heritage. By doing so, more people can realise Chinese lacquer art's charm and unique value.